Efficacy of traditional Chinese medicine injections for treating idiopathic pulmonary fibrosis: A systematic review and network meta-analysis. - Shuai-Yang Huang; Hong-Sheng Cui; Ming-Sheng Lyu; Gui-Rui Huang; Dan Hou; Ming-Xia Yu (PLoS ONE, 2022)
Background Idiopathic pulmonary fibrosis (IPF), acutely or slowly progressing into irreversible pulmonary disease, causes severe damage to patients' lung functions, as well as death. In China, Chinese medicine injections (CMIs) have been generally combined with Western medicine (WM) to treat IPF, which are safe and effective. This study aimed to systematically compare the efficacy of 14 CMIs combined with WM in the treatment of IPF based on a systematic review and network meta-analysis (NMA). Material and methods PubMed, Web of Science, Embase, Cochrane Library, MEDLINE, and Chinese databases, including the China National Knowledge Infrastructure, Wanfang Database, Scientific Journal Database, and China Biology Medicine Database were searched from inception to October 31, 2021. The inclusion criterion was randomized controlled trials (RCTs) on CMIs with WM for treating IPF. Reviewers independently screened the literature, extracted data, and evaluated the risk of bias in the included studies. RevMan 5.4 software and Stata software (version 16.0) were used for the data analysis. NMA were carried out for calculating the odd ratios (ORs) with 95% confidence intervals (CI), the surface under cumulative ranking curve (SUCRA) and the probabilities of being the best. Results A total of 63 eligible RCTs involving 14 CMIs were included in this NMA. More CMIs can significantly improve the clinical effectiveness rate (CER); Shuxuening injection (SXN)+WM (OR 8.91, 95% CI 3.81-20.83), Shuxuetong injection (SXT)+WM (OR 7.36, 95% CI 3.30-16.00), Shenxiong injection (SX)+WM (OR 5.42, 95% CI 2.90-10.13), Danhong injection (DH)+WM (OR 4.06, 95% CI 2.62-6.29), and Huangqi injection (HQ)+WM (OR 3.47, 95% CI 1.55-7.77) were the top five treatment strategies. Furthermore, DH +WM ranked relatively high in the SUCRA value of the nine outcome indicators, oxygen partial pressure (PaO2) (OR -13.39; 95% CI -14.90,-11.89; SUCRA 83.7%), carbon dioxide partial pressure (PaCO2) (OR -4.77; 95% CI -5.55,-3.99; SUCRA 83.3), orced vital capacity (FVC) (OR -1.42; 95% CI -2.47,-0.36; SUCRA 73.5%), total lung capacity (TLC) (OR 0.93; 95% CI 0.51,1.36; SUCRA 89.0%), forced expiratory volume 1/ forced vital capacity (FEV1/FVC%) (OR -10.30; 95% CI -12.98,-7.62; SUCRA 72.7%), type III collagen (IIIC) (OR 13.08; 95% CI 5.11,21.05; SUCRA 54.9%), and transforming growth factor (TGF) (OR -4.22; 95% CI -6.06,-2.37; SUCRA 85.7%) respectively, which seems to indicate that DH+WM had the highest likelihood of being the best treatment. Conclusions This review specified several CMIs combined with WM in the treatment of IPF in China. In contrast to glucocorticoids or antioxidants, CMIs combined with WM delayed the decline in lung function, maintained oxygenation and quality of life in patients with IPF. The combined use of DH, SXN, SX, and safflower yellow sodium chloride injection (HHS) with WM exerted a more positive effect in treating IPF than WM alone. However, there were limitations to the conclusions of this study due to quality control differences in the included trials.